A Thiazole Orange Derivative Targeting the Bacterial Protein FtsZ Shows Potent Antibacterial Activity - Sun, Ning; Lu, Yu-Jing; Chan, Fung-Yi; Du, Ruo-Lan; Zheng, Yuan-yuan; Zhang, Kun; So, Lok-Yan; Abagyan, Ruben; Zhuo, Chao; Leung, Yun-Chung; Wong, Kwok-Yin (Frontiers in Microbiology, 2017)
The prevalence of multidrug resistance among clinically significant bacteria calls for the urgent development of new antibiotics with novel mechanisms of action. In this study, a new small molecule exhibiting excellent inhibition of bacterial cell division with potent antibacterial activity was discovered through cell-based screening. The compound exhibits a broad spectrum of bactericidal activity, including the methicillin-resistant Staphylococcus aureus, vancomycin-resistant Enterococcus and NDM-1 Escherichia coli. The in vitro and in vivo results suggested that this compound disrupts the dynamic assembly of FtsZ protein and Z-ring formation through stimulating FtsZ polymerization. Moreover, this compound exhibits no activity on mammalian tubulin polymerization and shows low cytotoxicity on mammalian cells. Taken together, these findings could provide a new chemotype for development of antibacterials with FtsZ as the target.